Policentriška urbanistinė struktūra – strateginis Lietuvos ir EU prioritetas - Daunora, Zigmas Jonas (Journal of Architecture and Urbanism, 2007)
Polycentric urban structure as strategic priority for Lithuania and the EUThe paper discusses conditions for a polycentric development of cities and their systems. Suggestions for possible correction of our country’s regional structure considering changed external interaction course and demographic potential development tendencies. Reasoning is based on attitudes sustained by scientific and global practice which nowadays are respected in different international programmes. The following propositions of accomplished analysis can be formulated:1. Polycentric development of countries, regions and major cities is an approved strategy of sustainable development. This strategy is successfully evolved in Lithuania since 1957. During the period of intensive urbanization (1970–1990) it enabled to develop a group of small towns which became centres and subcentres of regions.2. New directions of international integration and a regressive demographic development of the country initiate correction of its regional structure for a better consolidation of demographic and material resources. Such opportunities are provided by: a) the growing role of Klaipėda city and region which is oriented to the Baltic region; b) the fact that the international communication corridors of Via Baltica and Rail Baltica, emphasizing the importance of the north-south direction, are becoming a reality.3. Urban planning and regional development require the government’s attention, adequate to the importance of the tasks to be solved. The country’s consolidated regional structure with 8 regions instead of 10, stronger Utena region, with growing seaport and Kaunas region, dominating in the centre of the country, would give more dynamics and opportunities for the progress of the state.Article in Lithuanian.Santrauka. Nagrinėjamos miestų ir jų sistemų policentriškos plėtros sąlygos. Iškeliamos kai kurios prielaidos galimai Lietuvos regioninės struktūros korektūrai, atsižvelgiant į pakitusias išorinės sąveikos kryptis bei demografinio potencialo raidos tendencijas. Samprotavimai paremti mokslo ir pasaulinės praktikos patvirtintomis nuostatomis, kurios dar 1957 m. buvo pradėtos diegti Lietuvos gyvenviečių sistemoje ir išlieka veiksmingu instrumentu darniai plėtojant šalies socialinį, kultūrinį ir eko nominį potencialą.Reikšminiai žodžiai: šalis, regionas, miestas, urbanistinė struktūra, policentriška plėtra.First published online: 21 May 2013